Mechanical performance of eco-efficient hollow clay bricks incorporating industrial nano-crystalline aluminium sludge. Issue 12 (14th October 2020) - Cavaco, Eduardo; Grilo, Inês; Paulo Gouveia, João; Júlio, Eduardo; Neves, Luís
Abstract: In this paper, mechanical properties of a new structural and eco-efficient hollow clay bricks are investigated. The principal goal was to recycle residual sludge from aluminium anodising industries by incorporating it in the raw material of bricks, thus contributing for the sustainability of the construction sector. It was also an objective to enhance thermal properties of the bricks, contributing to improve the energy efficiency of buildings, and maintain their mechanical properties. A large set of mechanical tests was conducted. A comparison between traditional, structural and the new eco-efficient bricks is established. Results show that the mechanical properties of the new bricks and masonry are not significantly affected by the aluminium sludge, thus allowing their use without strength limitations, and taking advantage from the thermal improved performance.